International judicial integration and fragmentation - Webb, Philippa (OUP OxfordGB, 2013)
Addresses three questions viz., are international courts engaged in the dialectic and do they render decisions that are largely coherent; what factors influence the degree of integration or fragmentation among international courts?; and what do the results of the first two questions tell us about the development of international law by international courts?